Trust in Archives– Trust in Digital Archival Content Framework - Donaldson, Devan Ray (Archivaria, 2019)
Trust in information found online matters now more than ever. The proliferation of fake news and “post-truths” makes it difficult for people to determine what is trustworthy. People even question digital versions of basic identity documents such as birth certificates, the processes that archivists use to preserve them, and attestations of their authenticity. Given the current landscape, we need to better understand trust in archival materials found online. Drawing from relevant literature, I developed a model to examine the relationship between trust in archives and trust in digital archival content, the Trust in Archives–Trust in Digital Archival Content (TIA-TDAC) Framework. This article outlines an empirical test of the TIA-TDAC Framework. Using measures of both levels of trust, I designed a survey to evaluate archives users and potential archives users’ trust in a diverse range of digitized and born-digital materials from a broad range of archives in the United States. Results of the survey indicate both that the association of trust in archives with trust in digital archival content could be empirically measured and that the relationship between the two trust levels was positively correlated. The article also discusses future directions for research. RÉSUMÉ La confiance accordée à l’information trouvée en ligne est maintenant plus importante que jamais. La prolifération des fausses nouvelles et des « post-vérités » fait en sorte qu’il est difficile pour les gens de cerner ce qui est digne de confiance. On remet même en question les versions numériques des pièces d’identité de base, comme les certificats de naissance, les procédés utilisés par les archivistes pour les préserver, et la certification de leur authenticité. Étant donné l’état actuel des choses, nous devons mieux comprendre la confiance accordée au matériel archivistique qui se trouve en ligne. Puisant dans les écrits pertinents, j’ai développé un modèle pour explorer la relation entre la confiance envers les archives et la confiance envers le contenu archivistique numérique, le cadre Confiance dans les archives-confiance dans le contenu archivistique numérique (CA-CCAN). Cet article souligne un test empirique du cadre CA-CCAN. En utilisant des mesures pour les deux niveaux de confiance, j’ai élaboré un sondage pour évaluer la confiance accordée par des utilisateurs et des potentiels utilisateurs d’archives à une variété de matériel numérisé et né numérique provenant d’une large sélection d’archives aux États- Unis. Les résultats du sondage démontrent à la fois que l’association entre la confiance accordée aux archives et la confiance accordée au contenu archivistique numérique peut être mesuré de façon empirique et que la relation entre les deux niveaux de confiance démontre une corrélation positive. L’article aborde également des orientations de recherche éventuelles.